THE INFLUENCE OF ARMADINE ON THE PERIPHERAL NERVE IN THE CORRECTION OF PAСLITAXEL-INDUCED NEUROPATHY IN THE EXPERIMENT - Ostrovskyi, M.M.; Deltsova O.І.; Gevka, O.I.; Herashchenko, S.B. (World of Medicine and Biology, 2019)
In the study of the subtle structure of the peripheral nerve in the correction of paclitaxel-induced neuropathy with armadine, it was established that, restoration of experimental paclitaxel-induced neuropathy in the peripheral nerve occurs in 3 periods. The first period lasts up to 28 days from and manifested by the restoration of the myelin nerve fibers. Among them there are demyelinated nerve fibers with destruction of the axial cylinder, their Schwann cells are vacuolated, the endoneurium is swollen. On the 21st-28th days the condition of mitochondria is normalized. Morphological signs of increased protein synthesis are present in Schwann cells. A small amount of damaged myelin nerve fibers remains. Characteristic of the third period are the newly formed nerve fibers of small and medium caliber with normal state of morphological structures. The number of nerve fibers of large caliber with signs of dystrophic processes increases, progressing atrophy of axial cylinders, manifestations of failure of regenerative processes.